The problem of political development in contemporary Arab countries (Damascus University Journal for the economic and Political sciences, 2021)
This study aims to analyze the problem of political development in contemporary Arab countries since its independence until today, by monitoring several crises that combined and formed a reason for the weakness of Arab political development. The study concluded that the majority of these crises are intended by Arab leaders Because of its rejection of reform policies that do not serve its interests, and the other part was the result of internal accumulations due to the historical context of the state, in addition to the external crises that have exacerbated the problem in the Arab region. At the end of the study, a strategy was proposed to activate the process of political development in the Arab countries, according to a specific development plan that ensures deep reforms in the political structure, economic system, and social and cultural construction.
Keywords: The problem of political development in contemporary Arab countries